FIGURATIVE LANGUAGE OF MAYBELLINE COSMETICS ADVERTISEMENT FOUND IN CATALOGUE ONLINE ON PINTEREST - Wibowo, Syamsuri Ari; Rosiani, Hilda (Dinamika : Jurnal Sastra dan Budaya, 2016)
Advertisement is a media communication which contains sign the most. In order to achieve the selling goals, companies will provide advertisement to introduce their product. In this matter, the thesis writer focuses on analyzing figurative language in advertisement. They are two objectives intended to be solved in this thesis, they are to describe types of figurative language and describe the meaning of figurative language in Maybelline cosmetics advertisement found in Pinterest. This study was conducted to analyze the uses of figurative language in Maybelline cosmetics of the catalogue online Pinterest. This study focuses on observing the words which contain figurative language by using Perrine’s theory. The method of this study uses descriptive qualitative because the researcher described the sentence that is categorized into figurative language. Whereas, data source were taken from advertisement catalogue online Pinterest which were publish on 2016 to 2018. The result of the data shows that there are eleven sentences which contain eight categorized figurative language and seventeen word that found in advertisement. The study found that there are eight kinds of figurative language which appeared in Maybelline advertisement such as: Personification, paradox, metaphor, apostrophe, symbol, allegory, hyperbole, and repetition. Keyword: Language, Figurative Language, Maybelline Advertisement